2000
DOI: 10.1096/fasebj.14.9.1109
|View full text |Cite
|
Sign up to set email alerts
|

The transactivation‐competent carboxyl‐terminal domain of AF‐9 is expressed within a sexually dimorphic transcript in rat pituitary

Abstract: We have investigated the biological role of the cellular counterpart of the leukemogenic AF-9 gene by cloning the rat AF-9 (rAF-9) cDNA and defining the regulation of an anterior pituitary-specific rAF-9 transcript that is expressed in a sexually dimorphic manner. Expression of this transcript is down-regulated after puberty in females and can be subsequently up-regulated in adults by ovariectomy. Hormone replacement studies have provided direct evidence that rAF-9 mRNA expression is suppressed by estrogen. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Particularly high levels of expression are noted in the spleen, and expression during embryogenesis appears highest in early embryos (Figure 4). These results are in general agreement with analyses of AF9 transcripts in humans and rats by Northern blot (Iida et al, 1993;Morgan et al, 2000).…”
Section: The Mouse Af9 Gene Is Nearly Identical To Human Af9 and Is Wsupporting
confidence: 89%
“…Particularly high levels of expression are noted in the spleen, and expression during embryogenesis appears highest in early embryos (Figure 4). These results are in general agreement with analyses of AF9 transcripts in humans and rats by Northern blot (Iida et al, 1993;Morgan et al, 2000).…”
Section: The Mouse Af9 Gene Is Nearly Identical To Human Af9 and Is Wsupporting
confidence: 89%
“…Within the anterior lobe, transgene transcripts are further restricted to a sub-population of cells indicating that the transgene is also able to mediate cell-type-specific transcriptional control. Thus, using a previously validated (Morgan et al 2000) dual ISH/ immunohistochemical technique we have demonstrated co-localization of the transgene transcript with LH -subunit immunoreactivity. This finding reflects our demonstration of Egr-1 protein in rat gonadotrophs (Knight et al 2000), and indicates a remarkable fidelity of cell-type-specific expression that is conferred by egr-1 sequences in the transgene.…”
Section: Discussionmentioning
confidence: 85%
“…1D). Dual ISH/immunocytochemistry (Allen et al 1997, Morgan et al 2000 using the LH -subunit antiserum in combination with the antisense GFP probe revealed co-localization of LH -subunit immunoreactivity with transgene mRNA (Fig. 1D).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Atlas Rat 1.2 cDNA Expression Arrays (Clontech Laboratories, Palo Alto, CA, USA), consisting of rat cDNA fragments from 1176 genes, were used in this study. Total RNA was extracted from a pool of 2 rat pineals sampled at either 12.00 h (L) or 24.00 h (D) using a standard protocol (16), and DNAse I‐treated according to the Atlas protocol. RNA quality was then assessed by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%